Assessment of a conventional 4L DC-DC Flying Capacitor Topology to operate in resonant mode and soft-switching capability - Medeiros, Augusto Manfroi (2024)
Multilevel resonant converters have been used to achieve high levels of power density and efficiency in low voltage (LV) step-down converters, due to the demand for high output currents and the benefits of soft-switching properties. These converters typically operate at or above the resonance frequency due to their characteristics. This work proposes an extension to the multilevel resonant floating capacitor (ML-RFLCC) converter, demonstrating the ability of a 1:3 converter to achieve soft-switching and output voltage regulation while operating at or below the resonance frequency. Due to the number of state variables, a state diagram is proposed to demonstrate the operation of the proposed converter, and its dependencies, on the different resonant tanks. To achieve these objectives, this work proposes an operating coefficient A. A prototype, employing GaN switches, is developed to validate the theoretical results and non-idealities while operating below the resonance frequency.